Peran Bendahara Pengeluaran Terhadap Kualitas Laporan Keuangan Dinas Pekerjaan Umum Dan Penataan Ruang Kota Sibolga - Syahriani Mewanti; Meily Surianti; Roslina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Expenditure Treasurer contributes to the creation of good governance and accountability as well as timely reporting and quality financial reports. It is best for an expenditure treasurer to have competent human resources, supported by an educational background in accounting, frequent education and training, and has experience in the financial sector. This research aims to determine the role of the expenditure treasurer on the quality of financial reports at the Sibolga City Public Works and Spatial Planning Service, in accordance with the phenomenon where there are still recording errors made by the expenditure treasurer, which affects the financial reports. The method used in this research is descriptive qualitative research, considering that in this research the researcher intends to understand the phenomenon of what the research subjects experience, and the researcher also uses two variables, namely expenditure treasurer with Knowledge and Skill indicators and relevant financial report quality variables, reliable, comparable and understandable. The results of this research show that the role of the treasurer for expenditures at the Public Works and Spatial Planning Service has an important role, although the Knowledge and Skill indicators are not yet optimal for the treasurer of the Sibolga City Public Works and Spatial Planning Service.